Relationships between Opposition and Powers in Tajikistan:History and Present Time - H. H. Khurramov (Проблемы постсоветского пространства, 2017)
After becoming independent the relationships between the official powers of Tajikistan and oppo- sition were shaping not easily. The opposition was, in fact, estranged from development and implementation of internal and foreign policy. The results of parliamentary elections conducted in March 2015 did not change the balance of political forces in the Tajik parliament. Moreover, the main opposition party failed to pass into the parliament which led to a new political situation in the country.